OTO-ENDOSCOPY FOR RESIDUAL DISEASE AFTER RADICAL AND MODIFIED RADICAL MASTOIDECTOMY FOR CHOLESTEATOMA * - Salahuddin Ayubi (Journal of University Medical & Dental College, 1970)
ABSTRACT Introduction: Oto-endoscopy is a new and latest introduction in the middle ear and mastoid surgery. Its application has not yet gained popularity in Pakistan and our study is first of its kind in Pakistan to evaluate the utility of oto-endoscope in canal wall down procedures. Objectives: To see whether the use of oto-endoscope helps in decision making to modify the procedure preoperatively or decrease the incidence of residual disease better than microscope in radical and modified radical mastoidectomy. Study design: Case series Patients and methods: ENT Unit, Madina Teaching Hospital, Faisalabad (A tertiary care hospital). Non-probability convenience sampling. Twenty patients in total. Results: Oto-endoscopy detected five cases of residual disease after modified radical mastoidectomy and one case after radical mastoidectomy. Conclusions: 1. Oto-endoscopy does influence the detection of residual cholesteatoma in sinus tympani, anterior epitympanum and protympanum. 2. It can also modify the decision to convert modified radical to radical mastoidectomy if required.